A new species of Cyllopsis R. Felder, 1869 from the highlands of Chiapas, Mexico (Lepidoptera: Nymphalidae: Satyrinae) - Warren, Andrew D.; Nakahara, Shinichi; Llorente-Bousquets, Jorge; Luis-Martínez, Armando; Miller, Jacqueline Y. (Zootaxa, 2018)
A new species of Cyllopsis R. Felder, 1869, is described and illustrated from the highlands of Chiapas, Mexico. Cyllopsis tomemmeli A. Warren & Nakahara, sp. nov., is currently known from 13 specimens (9 males and 4 females) collected on March 26–28, 1959, southeast of San Cristóbal de Las Casas. Despite extensive studies on the butterfly fauna of this region, this species has not since been encountered. We discuss possible relationships between this new species and other species of Cyllopsis.